Education in Human Rights: Reflections on Power, Violence and Authority in the School - Schilling, Flávia; Universidade de São Paulo (Pontificia Universidad Javeriana, 2007)
This article explores human rights and education based on an intervention experience conducted in three schools located in Sao Paulo City, which had as its main goal a substantial reduction in violence (2004-2005) . The guideline was that education should be considered a basic human right, ta- king into consideration the power and authority relations that exist within this institution. What are the problems that we face, nowadays, to consider education as a human right, in the difficult Brazilian history? Is it possible to think about some kind of democratic authority within the school, when our vision of authority is linked to despotic leaders, or even when there is no space for any authority? How does this discussion associate with the violence in our daily life in school? These are some of the questions included in the debate proposed by this article